(untitled) (Journal of the Digital Humanities Association of Southern Africa, 2023)
Despite many attempts to address the situation, South Africa’s official languages remain under-resourced in terms of the text and speech data required to implement state-of-the-art language technology. To ensure that no language is left behind, resource development should remain a priority until a strong digital presence has been established for all indigenous languages. This paper provides an overview of previous projects that were specifically aimed at speech resource development and introduces an ongoing initiative to launch South Africa’s languages on the Mozilla Common Voice platform.